Sunflower Uganda: Climate risk assessment - Demissie, Teferi Dejene; Duku, Confidence; Groot, Annemarie; Oroma, George W.; Osumba, Joab J.L. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Uganda’s agricultural sector is an important catalyst for economic growth, poverty alleviation, and food security. Nevertheless, the economic losses from the impacts of climate change on the agricultural sector by 2050 are estimated to be about US$1.5 billion (Zinyengere et al., 2016). Climate-smart agriculture practices present an opportunity to reduce such losses because it builds resilience in the agriculture sector, improves productivity and farmer incomes, and contributes to climate change mitigation (CIAT & World Bank, 2017).